ChemInform Abstract: 2‐Heteroaryl Benzimidazole Derivatives as Melanin Concentrating Hormone Receptor 1 (MCH‐R1) Antagonists. Issue 50 (10th December 2013) - Lim, Chae Jo; Kim, Jeong Young; Lee, Byung Ho; Oh, Kwang‐Seok; Yi, Kyu Yang
Abstract A novel series of 2‐hetaryl‐substituted benzimidazole derivatives (V) (15 examples) are synthesized and evaluated as MCH‐R1 antagonists.